Genetic association of the epidermal growth factor gene polymorphisms with peri-implantitis risk in Chinese population. Issue 1 (1st January 2021) - Chang, Zhongfu; Jiang, Dandan; Zhang, Shikun; Pei, Dongdong; Zhang, Zhirong; Zhang, Lihua; Cai, Jianying; Cao, Jun
ABSTRACT: Peri-implant disease is an inflammatory disease and is related to genetic heterogeneity. Considering the genetic association of epidermal growth factor ( EGF ) gene polymorphisms with the susceptibility of periodontitis, its genetic association with peri-implantitis risk in a Chinese Han population was explored. Three hundred individuals who underwent dental implants were recruited, and divided into healthy implant group and peri-implantitis group. The genotype and allele distribution of EGF gene rs2237051 and rs4444903 polymorphisms were analyzed via direct sequencing and the frequencies were compared between the two groups using chi-square test. No significant difference was detected for the clinical information between healthy implant group and peri-implantitis group, including lifestyle habits platform type and position, peri-implant phenotype, brushing time, dental floss, and mouth washing frequencies. Individuals with peri-implantitis had poor periodontal status. The GG genotype and G allele of rs2237051 showed significant increasing trend in peri-implantitis group compared with the healthy implant group. Compared with the AA genotype carriers, rs2237051 GG genotype carriers showed lower risk to suffer from peri-implantitis (OR = 0.236, 95%CI = 0.089–0.624), and possessed low values of gingival index, plaque index and calculus index, peri-implant pocket depth (PPD) and clinical attachment level (CAL). But there was no significant difference for the rs4444903 genotype distributions between the case and control groups. In summary, EGF rs2237051 polymorphism showed close association with the genetic background of peri-implantitis. Rs2237051 GG genotype and G allele might be protective factors for the onset of peri-implantitis.